RBI-IOWs integrated approach to risk assessment: Methodological framework and application. (October 2022) - Arena, Edoardo; Fargione, Giovanna; Giudice, Fabio; Latona, Elisa
Abstract: The planning of inspection and maintenance activities is a challenge that researches are largely addressed in petrochemical plants. The Risk-Based-Inspection (RBI) methodology, defined by the API 580 and API 581 Recommended Practices, is the main tool widely used for planning inspection and maintenance activities. However, the validity of the RBI results is closely related to the operating conditions that are supposed to remain constant throughout the inspection period. Significant efforts were made to improve the basic RBI approach. Uncertainty in forecasting models, accuracy in the assumptions of degradation-based approaches, subjective judgment and human error in risk assessment, lack of compliance with industry codes and standards, need to improve maintenance planning and inspection interval optimization, remain the key challenges to be addressed. A tool that can allow a dynamic approach to updating the inspection plan, by a real-time readjustment of the variation in the equipment's risk levels, in compliance with the oil and gas reference standards, is the API 584 Integrity Operating Windows (IOWs) methodology, through which critical windows are defined for the parameters considered to have the greatest impact on the equipment integrity. The adoption of this methodology is capable of overcoming the aforementioned limitations of the RBI, because the inspection plans can be directly modulated by monitored variations in the critical process parameters of the system under analysis. With these premises, the aim of the present study is to outline a fully integrated dynamic risk-based methodological framework to enhance the basic RBI approach by using IOWs analysis, which provides the basis for the development of a procedural model to be implemented in the inspection planning practice. Inspection and maintenance departments are the main beneficiaries, being aware of changes or upset during an operation running, which could give significant advantage in the identification of a not expected accelerated damage mechanism, and its critical effects. To show its application in improving the monitoring of critical plant parameters, which could limit the reliability of pressure equipment during their life cycle, reference is made to the PACOL-HF plant section of the SASOL factory located in Augusta (Italy). As a main result, the proposed approach and its procedural model prove effective in preventing the occurrence of undesired events, through both a real-time monitoring of the process variables, and the resulting mitigation actions that can avoid the failure of the equipment. Highlights: A new methodological approach to assess risk and plan inspections dynamically. Integration of Risk Based Inspection and Integrity Operating Windows. Improvement in monitoring the critical plant parameters. Verification of the methodology using real industrial case study.